(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
On May 12, 19 and 29, 2020, at the Faculty of Economic Sciences of the Koszalin University of Technology, the Scientific Conference of the Student Assosiation of the Faculty of Economic Sciences and Scientific Assosiations was held. The conference consisted of a series of online events on the following topics: "Security in cyberspace", "Saving and long-term investing", "Financial credibility - what can you gain? The role of the BIK”. The conference adopted the formula of a scientific debate, became a platform for the exchange of views for students, academic teachers and invited guests. The events were held under the honorary patronage of Prof. Jerzy Korczaj, PhD, Eng. - Dean of the Faculty of Economic Sciences, Koszalin University of Technology.